If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2z + -7) = 5z + 17 + 2 Reorder the terms: 3(-7 + 2z) = 5z + 17 + 2 (-7 * 3 + 2z * 3) = 5z + 17 + 2 (-21 + 6z) = 5z + 17 + 2 Reorder the terms: -21 + 6z = 17 + 2 + 5z Combine like terms: 17 + 2 = 19 -21 + 6z = 19 + 5z Solving -21 + 6z = 19 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. -21 + 6z + -5z = 19 + 5z + -5z Combine like terms: 6z + -5z = 1z -21 + 1z = 19 + 5z + -5z Combine like terms: 5z + -5z = 0 -21 + 1z = 19 + 0 -21 + 1z = 19 Add '21' to each side of the equation. -21 + 21 + 1z = 19 + 21 Combine like terms: -21 + 21 = 0 0 + 1z = 19 + 21 1z = 19 + 21 Combine like terms: 19 + 21 = 40 1z = 40 Divide each side by '1'. z = 40 Simplifying z = 40
| 3x+4x-6=2 | | (22x+253)/30=11 | | (X/4)=23 | | c/2+3=-2 | | 18+x=51 | | 3y^2+15y=42 | | c/2+3-3=-2-3 | | 15y-14y+5=6 | | 5x-11=9-(4-14) | | 2r^3-3r^2=32r-48 | | 4x-9=24-3 | | 3/5x-10=-1 | | 4x-6(2x+3)=-2 | | 18.9=23.9 | | 36/60=45/x | | 37=32-2c | | 13.78-.8a=0 | | 16=8(x-1)-8 | | x/7-5/4=x/14-1/28 | | 19z-18z=16+22 | | 7(m-3)-5m=2(m-10)-1 | | 1/2x27 | | 2(x+2.3)=x+6.4 | | 10+(-5)= | | 9x+3-6x-5=19 | | y+46=28 | | 3a+5=15 | | 3(x+4)+6=27 | | 1.1+8.8=5.9a-4.9a+4.9 | | z+3=5 | | x^2-12x+100=0 | | 6(3n+3)=6(9n+3)+3 |